Left-sided gastroschisis without eviscerated organs - Lava Abdullah; Raeyk Abbas (Elsevier, 2022)
Left sided: gastroschisis is a rare malformation which is defined as presence of abdominal wall defect. This malformation usually occurs to the right side of the umbilicus. Its occurrence to the left side is more rare and usually it is accompanied with other findings.We presented a case of a left-sided gastroschisis with no eviscerated organs which represent the first case in the literature, and it was managed surgically.